Biblioteca de propriedades termodinâmicas para substâncias de Van der Waals em linguagem Julia - Silvestri, Giovanni de Medeiros (2021)
Thermodynamic properties are constantly used to calculate, design, and describe processes and phenomena, consequently, property libraries are used as tools for these works, providing speed and practicality. The algorithms of these libraries are based on equations of state. An existing model of this type of equation is the van-der-Waals model, which in addition to using only two constants, presents an exact solution for the transition of liquid-vapor phase through the Gibbs solution to the Maxwell construction and has a dimensionless form dependent only of the critical properties of the substance, which makes it possible to work with substances that have little known experimental data. The bibliographic review carried out indicates the apparent lack of libraries that implement this model. Therefore, the objective of this work is to implement a property library with this equation of state. For the development of the library, using the context of speed and practicality mentioned, it was decided to use the Julia language in the implementation, since it is a high-level language that also has high performance, is dynamic and with a syntax very close to mathematics, constituting itself as a science-oriented language, and so far, the bibliographic review carried out indicates the apparent absence of a property library native in that language.